Totus Christus, Kenosis, dan Ekaristi: Sebuah Imajinasi Eklesiologis Baru - Angga Avila (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2022)
Covid-19 pandemic changes the way the world sees reality. Much research has shown that the pandemic also affects the way people see the life of the church, especially as it has driven many people out of the church. This paper offers a sacramental ecclesiology based on totus Christus as the ontological basis for a “proflective” church—a suggestive portrayal previously offered by Joas Adiprasetya, which encourages the church to learn and unlearn by becoming vulnerable. If the church is the body of Christ, what is the fate of those who left the church? Is it possible for the body of Christ to be broken down and separated? Seeing the church as Christ’s body that participates in the historical Eucharist through Hans Urs von Balthasar’s reflection on Mysterium Triduum, this paper thus offers an ecclesiological imagination of the church as proflective and Eucharistic to account for those who have left the church and to challenge the postpandemic church to think and live in a truly Christlike (and trinitarian) way.